The Influence of Product Innovation, Product Quality, and Price on Repurchase Decision at Elegant Guitar with Customer Satisfaction as an Intervening Variable - Fakhri Lesmana; Endang Sulistya Rini; Fadli (Indonesian Journal Publisher, 2025)
MSMEs are the leading sector of the Indonesian economy in achieving Indonesia's National Economic Growth. The problematic phenomenon faced by the MSME industry such as Elegant Guitar is the low level of sales due to weak repurchasing decisions from customers. The purpose of this study is to determine and analyze the effect of product innovation, quality of product, and price on Repurchase decisions through customer satisfaction at Elegant Guitar. This type of research is associative research and the data used is quantitative data. The research sample is 286 Elegant Guitar customers. The data analysis used is Partial Least Square Structural Equation Modeling. The results of the study directly show that product innovation has a negative and insignificant effect on customer satisfaction, product quality has a positive and significant effect on customer satisfaction, price has a positive and significant effect on customer satisfaction, product innovation has a negative and insignificant effect on repurchase decision, product quality has a positive but insignificant effect on repurchase decision, price has a positive and significant effect on repurchase decision, product innovation has a negative and insignificant effect on repurchase decision through customer satisfaction, product quality has a positive but insignificant effect on repurchase decision through customer satisfaction, and price has a positive but insignificant effect on repurchase decision through customer satisfaction.